School Guidance Services: A case study - Can, Ertuğ; Nikolayidis, Urania (Fırat University, 2021)
The aim of this research is to determine the current status of school guidance services according to the opinions of teachers working in public institutions. Qualitative research method was used in the research. The study group of the research consists of 32 guide teachers working in Istanbul in the 2018-2019 academic year. The data of the study were collected through face-to-face interviews with the help of 5 open-ended questions and evaluated by content analysis. Teachers' opinions on the state of school guidance services were analyzed under 9 themes. According to the results of the research, school guidance services provide important contributions to the solution of problems by providing the personal, social and psychological development of students. School guidance services contribute positively to reducing the workload of school administrators, solving the problems faced by teachers with students, educating parents and strengthening their relations with students, and raising public awareness. According to the result of the research, factors affecting school guidance services are listed as teachers, parents, administrators, environment, students, social perception, legal regulations, awareness of guidance and working conditions. According to the results of the research, legal regulations should be made, school counselors should work effectively, parents, teachers and school administrators should be informed and school guidance services should be made widespread in order to carry out school guidance services more effectively.

Bu araştırmanın amacı, resmî kurumlarda görevli öğretmenlerin görüşlerine göre okul rehberlik hizmetlerinin mevcut durumunu belirlemektir. Araştırmada nitel araştırma yöntemi kullanılmıştır. Araştırmanın çalışma grubu, 2018-2019 öğretim yılında İstanbul’da görevli 32 öğretmenden oluşmaktadır. Araştırmanın verileri 5 açık uçlu soru yardımıyla yüz yüze görüşme yapılarak toplanmış ve içerik analizi ile değerlendirilmiştir. Öğretmenlerin okul rehberlik hizmetlerinin durumuna ilişkin görüşleri 9 tema altında analiz edilmiştir. Araştırma sonuçlarına göre okul rehberlik hizmetleri, öğrencilerin kişisel, sosyal ve psikolojik gelişimlerini sağlayarak sorunların çözümüne önemli katkılar sağlamaktadır. Okul rehberlik hizmetleri okul yöneticilerinin iş yükünün azaltılmasında, öğretmenlerin öğrencilerle karşılaştıkları sorunların çözümüne, velilerin eğitilmesine ve öğrencilerle ilişkilerinin güçlendirilmesine, toplumun bilinçlendirilmesine olumlu katkı sağlamaktadır. Araştırma sonucuna göre, okul rehberlik hizmetlerini etkileyen faktörler öğretmenler, veliler, yöneticiler, çevre, öğrenciler, toplumsal algı, yasal düzenlemeler, rehberlik bilinci ve çalışma koşulları olarak sıralanmıştır. Araştırma sonucuna göre, okul rehberlik hizmetlerinin daha etkili yürütülebilmesi için yasal düzenlemeler yapılmalı, rehber öğretmenlerin etkili çalışması sağlanmalı, veliler, öğretmenler ve okul yöneticileri bilgilendirilmeli ve okul rehberlik hizmetleri yaygınlaştırılmalıdır.
OKUL REHBERLİK HİZMETLERİ: BİR DURUM ÇALIŞMASI